If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7d + -4d + -4d + -6 = 2d Reorder the terms: -6 + 7d + -4d + -4d = 2d Combine like terms: 7d + -4d = 3d -6 + 3d + -4d = 2d Combine like terms: 3d + -4d = -1d -6 + -1d = 2d Solving -6 + -1d = 2d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-2d' to each side of the equation. -6 + -1d + -2d = 2d + -2d Combine like terms: -1d + -2d = -3d -6 + -3d = 2d + -2d Combine like terms: 2d + -2d = 0 -6 + -3d = 0 Add '6' to each side of the equation. -6 + 6 + -3d = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -3d = 0 + 6 -3d = 0 + 6 Combine like terms: 0 + 6 = 6 -3d = 6 Divide each side by '-3'. d = -2 Simplifying d = -2
| 11x+2=14x-10 | | 10y=40x+3xy | | 2(t-2)=6 | | 7x-y=(x) | | 0.5(x+2)-(3x+8)=1.6(x-2)+9 | | 3(7x+20Y)+7(-3x+6y)= | | y-37=-67 | | -21=n-10 | | 2(2x+5)=40 | | 3(x-5)=2(x+1)+x | | 5+9x=-13 | | -5.7-44.2=-8.3v | | -7y+3=8y+1 | | 3(7x+20Y)7(-3x+6y)= | | 4x+8-3x-10=-33 | | -6-2x-1=4x+8-6x-3 | | 2(n+5)=11 | | 7=-11+3(6+5) | | 2(n+5)=111 | | -5r-r=5r-8 | | 3x+5x+4x-2=10 | | -10x+8-6x=-2-17x+9 | | 5.4x+8.6=3.4x-16 | | (10+2x)(20+2x)=336 | | 7x+6=3x+2 | | 2x-16y=7 | | 6(6g-2)+8(1+5g)=2g | | 6n-32=3n+7 | | 2x^2-4x=1.33333 | | 7t-6=330 | | (7+u)(5u-6)=0 | | 7x+8x+2x=12 |